The real effect of state corporate tax rate changes: Evidence from corporate headquarters relocation - CHOW, Travis K. (Institutional Knowledge at Singapore Management University, 2017)
The state tax apportionment formula used to determine state taxes is a function of the taxable income attributable to the state and state corporate tax rates. In this study, we rely on changes in state corporate income tax rates and other inducements across time and states as a quasi-natural experiment to examine the effect of state taxation on corporate headquarters (HQ) relocation. We find that changes in HQ state corporate income tax rates significantly affect the likelihood of cross-state HQ relocation. Other inducements also reduce the likelihood of relocation. The results of the cross-sectional analysis suggest that the likelihood of HQ relocation is less affected by changes in HQ state corporate tax rates when (i) the state-level factor weights used to determine income attributable to the state favor property and payroll and (ii) the firm engages in tax planning to reduce taxable income. We contribute to the literature on corporate tax planning by providing further evidence of how state taxation policies affect real corporate decisions that have significant economic consequences for the state.